2009
DOI: 10.1111/j.1475-6773.2009.00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to the Use of Health Services Research in Policy

Abstract: The pathways open up what too often is an unexplored "black box" that mediates between health services research and its use by policy makers. Such pathways can help stakeholders to bridge different perspectives in ways that strengthen the possibility that effective research will be supported and used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 24 publications
2
85
0
2
Order By: Relevance
“…Participants' frequent mention of intermediaries (e.g. non-profit and advocacy groups, health departments) as trusted and valued sources of information is echoed in the literature and illustrates the vital role that these groups play in policy development, often serving as a bridge between researchers and policymakers [12,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Participants' frequent mention of intermediaries (e.g. non-profit and advocacy groups, health departments) as trusted and valued sources of information is echoed in the literature and illustrates the vital role that these groups play in policy development, often serving as a bridge between researchers and policymakers [12,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Both formal and informal networks are needed to facilitate the transfer of research knowledge to decision-makers 100 and improved collaboration and communication between GDs and CRGs might facilitate the use of Cochrane Reviews in the development of guidelines. Previous research has identified a number of potential facilitators for increasing the impact of systematic reviews on the policy-making process.…”
Section: Implications Of the Findingsmentioning
confidence: 99%
“…Despite this, there appears to remain a gap between the world of research and the world of health policy that has been frequently observed, and lamented. [1][2][3][4][5][6] Civil servants, who are in many ways the customers for health research, have difficulty in communicating effectively with the research community. [7][8][9] A survey of the situation in Europe with regard to health services research in 2009-2010 revealed a remarkably varied picture and poor use of such research by policy-makers, except with regard to new drugs.…”
Section: Introductionmentioning
confidence: 99%